Reflections on the regulatory field covering the development of paediatric medicinal products: a brief overview of current status and challenges - Lehmann, Birka (Frontiers in Pharmacology, 2024)
Many medicinal products are initially developed and tested in adults, and there often exists only a limited amount of data on their safety and efficacy in children. Consequently, paediatric healthcare providers sometimes need to make informed decisions about using medicinal products in children based on available fragmentary data.Ethical guidelines emphasize the importance of protecting children and ensuring they receive safe and effective medical treatments. Paediatric clinical trials should be conducted to provide evidence-based care with specific attention to minimize risks to children.This highlights the dilemma of finding a balance between protecting children and adolescents (and avoiding unnecessary clinical trials) and obtaining reliable, robust and justified data to treat them adequately and not in an off-label manner with unknown risks.Paediatricians for years maintained that children and adolescents are not treated based on scientific up-to-date knowledge and justification. The slogan 'children are not small adults' 1 summarized the concerns in a catch phrase. Several actions to address this concern have been taken by different stakeholders. On a global level the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH), bringing together the regulatory authorities and pharmaceutical industry, developed and finalised the ICH guideline E 11 'Guideline on the Clinical Investigation of Medicinal Products in the Pediatric Population in 2000 2 .Governments recognized the necessity for legal provisions to support the development of medicinal products for children and adolescents. The United States (US) 3 and the European Union (EU) 4 have implemented legal requirements mandatory for new medicinal products and optional for known medicinal products intended for paediatric use. Several other countries have followed this approach to take special care for the treatment of children and